Development and Adsorption Characterization of Metal Affinity-Immobilized Magnetic Liposome. (11th February 2020) - Lu, Yuan; Liao, Dankui; Feng, Xuezhen; Meng, Hualin; Lu, Yuting; Wei, Qiqiu; Duan, Siliang; Wu, Shanguang
Abstract : A metal affinity-immobilized magnetic liposome (MA-IML) was prepared in this research, which was with lipid and Ni 2+ content of 143.25  μ g/mg and 32  μ mol/mg, respectively. The antihypertensive peptides Ile-Pro-Pro (IPP) and Val-Pro-Pro (VPP) could be adsorbed onto MA-IML under specific conditions, and the adsorption kinetics was explored. The pseudo-second-order kinetics (R 2   value > 0.98 ) was more suitable to describe the adsorption process of IPP and VPP than the intraparticle diffusion model and pseudo-first-order kinetic model. The results indicated that MA-IML could be used as an adsorbent for screening antihypertensive peptides from natural products.